Pembentukan Identitas Nasional Generasi Muda Melalui Kegiatan Karang Taruna Di Desa Padang Jaya Kabupaten Bengkulu Utara - Astuti, Hilda Rahmah Rahayu; Qurniati, Amnah (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to examine how the activities of Karang Taruna (Youth Organization) in Padang Jaya Village, North Bengkulu Regency, contribute to shaping the national identity of young people. National identity reflects the values of the nation embedded in every citizen, and Karang Taruna plays a crucial role in instilling these values through various social, cultural, religious, and entrepreneurial activities. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The informants in this study include Karang Taruna administrators, community leaders, the village head, and youth members. The findings reveal that activities such as the Ramadan Market, Independence Day celebrations, social services, and religious events have successfully fostered Pancasila values and strengthened patriotism, solidarity, and unity among youth. Challenges include limited active participation and inadequate facilities. However, these obstacles are addressed through collaborative efforts with the village government and the implementation of more inclusive programs. In conclusion, Karang Taruna has significantly contributed to the development and reinforcement of national identity among rural youth.